Rekonstruksi Hukum Ekonomi Syariah terhadap Bitcoin sebagai Instrumen Transaksi dan Investasi Digital - Sabrina Nur Baiti; Adhiningdyah Mulyani Taufiqs; Waluyo Waluyo (Moral : Jurnal kajian Pendidikan Islam, 2025)
The rapid growth of digital financial technology has introduced new economic instruments that require re-evaluation through the lens of Islamic economic law, one of which is Bitcoin. This study aims to analyze the legal standing of Bitcoin as a means of transaction and investment using a normative legal approach. Data were obtained through extensive literature review involving primary and secondary sources, including Islamic jurisprudence, maqāṣid al-sharī‘ah, qawā‘id fiqhiyyah, official fatwas, and contemporary technological and economic studies. The analysis employed normative and reconstructive methods to assess the compatibility of Bitcoin’s characteristics with the principles of Islamic law. The findings indicate that Bitcoin may be classified as a form of digital māl because it possesses utility, can be lawfully owned, and is tradable within open market mechanisms. However, its extreme price volatility, limited public acceptance, and absence of state-backed legitimacy make it unsuitable as a lawful medium of exchange in Islamic transactions. Conversely, Bitcoin may be permitted as an investment instrument under strict conditions, provided the activity avoids speculative motives, ensures transparency, and follows prudent financial conduct. Based on these assessments, this study concludes that Bitcoin is more appropriately categorized as a digital commodity rather than a transactional currency. This research contributes conceptually to the development of sharia-compliant crypto-asset regulations and opens avenues for further exploration on designing more stable and ethically aligned digital financial instruments.